Information Literacy Skills and Self-Efficacy of Pre-Service Islamic Primary Teachers Based on Engagement with Children’s Literature - Andi Hasrianti; Ridwan Andi Mattoliang (Al Ibtida: Jurnal Pendidikan Guru MI, 2026)
Background: Engagement with children’s literature has been recognized as an important factor in supporting literacy development and professional growth among pre-service teachers. However, limited empirical evidence is available regarding its contribution to information literacy skills and self-efficacy in teacher education contexts. Aims: This study aimed to analyze the effect of pre-service Islamic primary teachers’ engagement with children’s literature on information literacy skills and self-efficacy. Methods: A quantitative correlational design was employed. The participants were 38 students enrolled in the Primary Islamic Teacher Education Program during the odd semester of the 2025/2026 academic year at a higher education institution in Makassar, Indonesia. Participants were selected using total sampling. Data were collected through an information literacy test, a children’s literature engagement questionnaire, and a self-efficacy questionnaire. Data were analyzed using descriptive statistics and simple linear regression with a bootstrap procedure (5,000 resamples; 95% BCa confidence interval). Results: The findings revealed that engagement with children’s literature had a positive and significant effect on information literacy skills (B = 0.226, p = .011, 95% BCa CI [0.005, 0.375]), explaining 18.2% of the variance (R² = .182). Engagement with children’s literature also had a positive and significant effect on self-efficacy (B = 0.959, p < .001, 95% BCa CI [0.630, 1.251]), explaining 61.6% of the variance (R² = .616). The findings indicate a stronger effect on self-efficacy than on information literacy skills. Conclusions: Engagement with children’s literature contributes significantly to the development of pre-service teachers’ information literacy skills and self-efficacy. Integrating children’s literature into teacher education programs may serve as a sustainable strategy for strengthening both cognitive and affective competencies that support future teaching practice.